2017
DOI: 10.1097/rli.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Performance in the Course of Hypertrophic Cardiomyopathy

Abstract: Left atrial functional abnormalities are associated with LV fibrosis, but not with LV hypertrophy. While LA conduit function is impaired in early HCM stages as represented by mild or absent LV fibrosis, LA contractile function is impaired later in the course of disease progression as demonstrated by the presence of severe LV fibrosis only. These novel markers of LA performance may potentially proof useful for disease staging and early detection of cardiac deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
3
21
0
1
Order By: Relevance
“…Booster strain and SR, however, were also decreased in our HCM patients, which differed from the findings in [ 20 ]. In a recent study, Kowallick et al [ 40 ] characterized LA strain in HCM according to the extent of LV hypertrophy and fibrosis, and found that LA booster pump function was impaired in HCM with severe late gadolinium enhancement (LGE) only (LGE ≥ 20%). Indeed, our HCM subjects may represent those with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Booster strain and SR, however, were also decreased in our HCM patients, which differed from the findings in [ 20 ]. In a recent study, Kowallick et al [ 40 ] characterized LA strain in HCM according to the extent of LV hypertrophy and fibrosis, and found that LA booster pump function was impaired in HCM with severe late gadolinium enhancement (LGE) only (LGE ≥ 20%). Indeed, our HCM subjects may represent those with more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the human heart, it appears that LV systolic function largely influences LA reservoir function while LV relaxation and compliance are key modulators of atrial conduit and contractile functions [ 15 , 24 , 25 ]. Previous studies of echo and FT CMR in HCM adult patients consequently presented the reduction of all indices of LA dynamics [ 15 , 26 ]. Our results revealed that the majority of LA volumetric and functional indices were significantly compromised in HCM children compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Kowallick et al demonstrated the feasibility of applying CMR FT for analysing biatrial mechanics in healthy subjects [ 14 ]. They also reported that fibrosis played a larger role than hypertrophy in the development of LA dysfunction in adults with HCM [ 15 ]. Despite this progress, contemporary knowledge of LA and especially RA dynamics in a juvenile population with HCM remains rudimentary.…”
Section: Introductionmentioning
confidence: 99%
“…HFpEF and controls were compared, and male controls were compared with age-matched female subjects from a previous study with regard to LA and LV function. 23,26 Pearson (r) and Spearman (ρ) tests were used to find factors associated with VO2max. Univariate linear regression analysis and stepwise forward multivariable linear regression analysis were performed to search and control for influencing factors of VO2max in the whole cohort and partial correlation was analyzed.…”
Section: Statisticsmentioning
confidence: 99%